MORAL AND POLITICAL THREATS AFFECTING THE STABILITY OF SOCIETY - Muhammadolim Muhammadsidikov (Scholar Express Journal, 2023)
Ensuring the security of society and the stability of the country in the conditions of globalization is an urgent problem of today. In this article highlights of moral and political threats affecting the stability of society
Keywords: Socio-Political Process; Missionary; Security